2010
DOI: 10.2166/wst.2010.498
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between land use and water quality in a small watershed in South Korea

Abstract: Recent research and monitoring undertaken by various institutions have emphasized measurements of river-water quality. Based on the results, government agencies have set guidelines to improve river-water quality management. However, the relationship between water quality and land use/land cover (LULC) has not been examined closely in South Korea to date. This study investigated this relationship in the Imgok River watershed. For this study, the relationship between water quality parameters, e.g. metallic ions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 13 publications
3
5
0
3
Order By: Relevance
“…It denotes that fragmented urban landscapes can result into water pollution. Previous findings have reported close relationships between the proportion of built-up land uses and degraded water quality 20 21 22 , which is similar with the results in low water period in our study. Our study showed that the regional water quality was relatively worse in the district due to its higher population density and higher urbanization ratio.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It denotes that fragmented urban landscapes can result into water pollution. Previous findings have reported close relationships between the proportion of built-up land uses and degraded water quality 20 21 22 , which is similar with the results in low water period in our study. Our study showed that the regional water quality was relatively worse in the district due to its higher population density and higher urbanization ratio.…”
Section: Discussionsupporting
confidence: 92%
“…Land use changes in watersheds influenced all water quality indicators but these effects were idiosyncratic for each parameters 23 . Like previous studies 20 24 25 , our study demonstrated that a number of land use configuration metrics were significantly related to water quality parameters in Huzhou City.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In agricultural lands, however, sources of pollution are of different nature-diffuse or point. Nutrients may derive from both field crops and animal husbandry, and they have different nutrient ratios, as also indicated by Lee [70] and Jones [10]. At the same time, bottom sediments collected from sites included in cluster 3 have the highest average TN, TOC, Ca and Fe concentrations and also high TP concentrations (Table 10).…”
Section: The Relationships Between Water Quality Parameters and Land Usementioning
confidence: 70%
“…PCA has been widely used to determine the spatio-temporal patterns of climatic variables [9]. The relationship between water quality parameters and land use types were evaluated by correlation analysis and PCA in South Korea [10]. PCA analysis was also used to regionalize the seasonal variation in the monthly precipitation data from 1931 to 1990 at 85 stations in Turkey [11].…”
Section: Introductionmentioning
confidence: 99%